Neoliberal governmentality and the respatialisation of childcare in Ireland - Gallagher AM (PERGAMON-ELSEVIER SCIENCE LTD)
While geographers have contributed greatly to knowledge of the unequal effects of childcare delivery for parents and children as service users, the changing form this provision has taken over the last 10. years has received much less attention. Drawing on the emergence of a formalised childcare sector in Ireland since the late 90s, this paper explores the considerable political work which has taken place to prioritise centre-based care services over an established informal childminding sector. Rather than view this change as the outcome of a capitalist logic which scripts the inevitable shift towards larger, more rationalised services under processes of neoliberalisation, this paper calls for a closer examination of the way in which childcare is being respatalised through policy. Justified through a discourse of 'sustainability', governmental intervention in Ireland has sought to produce a new marketised childcare infrastructure which will operate without continued state support. The emerging infrastructure has been premised on the creation of centre-based facilities, through which forms of neoliberal governance have been introduced into the sector. It is suggested that the prioritisation of centre-based care over existing informal provision has served to introduce significant financial vulnerabilities to the sector at a time of economic uncertainty. © 2011 Elsevier Ltd.
Keywords: 16 Studies in Human Society